Confessions of a dangerous mind - Clooney, George; Kaufman, Charlie, 1958-; Rockwell, Sam; Barrymore, Drew; Barris, Chuck; Wurman, Alex; Miramax Films; Miramax Home Entertainment (Firm); Buena Vista Home Entertainment (Burbank, CA : Miramax Home Entertainment, 2003)
The outrageous life and careers of television producer and game show host, Chuck Barris.
Based on the book by Chuck Barris.
Originally released as a motion picture in 2002.
Features: deleted scenes, Chuck walks behind the set, Sam Rockwell screen test, audio commentary, Gong show acts, the real Chuck Barris, still gallery.
Director of photography, Newton Thomas Sigel ; production designer, James D. Bissell ; editor, Stephen Mirrone ; music, Alex Wurman.
Sam Rockwell, Drew Barrymore, George Clooney, Julia Roberts, Rutger Hauer, Maggie Gyllenhaal, Robert John Burke, Jennifer Hall.
MPAA rating: R.
Keywords: Barris, Chuck -- Drama; Barris, Chuck -- Film and video adaptations; Video recordings for hard of hearing people; Based on the book; Feature films; Biographical films